2020
DOI: 10.3892/etm.2020.9079
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA NEAT1 promotes apoptosis and inflammation in LPS‑induced sepsis models by targeting miR‑590‑3p

Abstract: Sepsis is a complication of infection caused by disease or trauma. Increasing evidence have shown that long noncoding RNAs (lncRNAs) are involved in the regulation of sepsis. However, the mechanism of lncRNA nuclear enriched abundant transcript 1 (NEAT1) in the regulation of sepsis progression remains to be elucidated. Lipopolysaccharide (LPS) was used to induce a sepsis cell model. The expression levels of NEAT1 and microRNA (miR)-590-3p were determined by reverse transcription-quantitative PCR. Cell viabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 41 publications
(54 reference statements)
0
18
0
Order By: Relevance
“…For example, NEAT1 was reported to be highly expressed in Parkinson's disease, and NEAT1 knockdown inhibited PD progression via regulating the miR-212-3p/axin 1 signaling pathway ( 24 ). NEAT1 also accelerated apoptosis and inflammation in lipopolysaccharide-induced sepsis models by targeting miR-590-3p ( 25 ). In the present study, NEAT1 was found to be upregulated in the TGF-β1-treated HPAEpiC and BEAS-2B cell lines, suggesting that the high expression level of NEAT1 could be associated with pulmonary fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…For example, NEAT1 was reported to be highly expressed in Parkinson's disease, and NEAT1 knockdown inhibited PD progression via regulating the miR-212-3p/axin 1 signaling pathway ( 24 ). NEAT1 also accelerated apoptosis and inflammation in lipopolysaccharide-induced sepsis models by targeting miR-590-3p ( 25 ). In the present study, NEAT1 was found to be upregulated in the TGF-β1-treated HPAEpiC and BEAS-2B cell lines, suggesting that the high expression level of NEAT1 could be associated with pulmonary fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis is essential for the selective elimination of cells, and it plays an important role in the occurrence and development of acute lung injury. The inhibition of lung cells apoptosis might increase the animal survival rate in LPS-induced acute lung injury [ 29 ]. DEX pretreatment ameliorated LPS-induced lung inflammation and oxidative stress by activating the Nrf2/Keap1 signaling pathway and regulating the expression of antioxidant genes [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Ma et al (2019) reported that miR-590-3p inhibited TNFRAF-6 to attenuate acute kidney injury in septic mice. MiR-590-3p also inhibited the LPS-induced sepsis apoptosis and inflammation (Liu et al, 2020b). In our study, miR-590-3p as a sponge to regulate inflammatory response of SAP and we did not discuss the function of miR-590-3p alone in SAP inflammation.…”
Section: Discussionmentioning
confidence: 66%
“…MiRNAs lead to translation inhibition of a large number of genes by sequence-specific binding to the 3'untranslated regions (UTRs) of homologous mRNAs (Pu et al, 2019). It is reported that miR-590-3p is an interesting gene that play an exactly opposite effect in different cancers (Ge and Gong, 2017;Salem et al, 2018) and also have function in inflammation injury (Liu et al, 2020b). But there have been no related reports in SAP.…”
Section: Introductionmentioning
confidence: 99%